Synthesis of Polytetrahydrofuran Using Protonated Kaolin as A Solid Acid Catalyst - Abdelhak Moumen; Zhour Hattab; Youghourta Belhocine; Kamel Guerfi; Nacer Rebbani (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
In this work, a non-toxic protonated kaolin clay exchanged with protons, was successfully applied as a solid acid catalyst for the polymerization of tetrahydrofuran (poly(THF)) at room temperature in the presence of acetic anhydride. Prior to using the kaolin as a catalyst, it was treated with HCl (0.1 M) and characterized using various analytical techniques. The amounts of catalyst and reaction time on the conversion of THF were investigated. Characterizations of nuclear magnetic Resonance of proton (1H-NMR), Fourier Transform Infrared spectroscopy (FT-IR), X-ray Diffraction (XRD), Optical Microscopy (OM), and Differential Scanning Calorimetry (DSC) techniques were used to examine the resulting polymer. X-ray characterization and DSC data indicated that the obtained poly(THF) is a highly crystalline substance. The results showed that protonated kaolin (kaolin–H+) has a high catalytic activity for the polymerization of THF with a conversion rate of 50.02% after 20 hours.